Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To determine which option represents the exact value of [tex]\(\tan \left(\frac{\pi}{12}\right)\)[/tex], we start by understanding the tangent value for the angle [tex]\(\frac{\pi}{12}\)[/tex].
The angle [tex]\(\frac{\pi}{12}\)[/tex] radians can be expressed in degrees as [tex]\(15^\circ\)[/tex] since [tex]\(\frac{180^\circ}{12} = 15^\circ\)[/tex].
Using known trigonometric identities, one approach to find [tex]\(\tan 15^\circ\)[/tex] is recognizing that [tex]\(15^\circ\)[/tex] can be represented as the difference between two familiar angles: [tex]\(45^\circ\)[/tex] and [tex]\(30^\circ\)[/tex]. Therefore, we can use the tangent subtraction formula:
[tex]\[ \tan(a - b) = \frac{\tan a - \tan b}{1 + \tan a \tan b} \][/tex]
For [tex]\(a = 45^\circ\)[/tex] and [tex]\(b = 30^\circ\)[/tex]:
[tex]\[ \tan 15^\circ = \tan (45^\circ - 30^\circ) = \frac{\tan 45^\circ - \tan 30^\circ}{1 + \tan 45^\circ \tan 30^\circ} \][/tex]
We know the tangent values:
[tex]\[ \tan 45^\circ = 1 \quad \text{and} \quad \tan 30^\circ = \frac{1}{\sqrt{3}} \][/tex]
Substituting these into the formula gives us:
[tex]\[ \tan 15^\circ = \frac{1 - \frac{1}{\sqrt{3}}}{1 + 1 \cdot \frac{1}{\sqrt{3}}} = \frac{1 - \frac{1}{\sqrt{3}}}{1 + \frac{1}{\sqrt{3}}} \][/tex]
To simplify the fraction, we'll first combine the terms in the numerator and denominator to have a common denominator of [tex]\(\sqrt{3}\)[/tex]:
[tex]\[ \tan 15^\circ = \frac{\frac{\sqrt{3} - 1}{\sqrt{3}}}{\frac{\sqrt{3} + 1}{\sqrt{3}}} = \frac{\sqrt{3} - 1}{\sqrt{3} + 1} \][/tex]
Next, we rationalize the denominator by multiplying both the numerator and the denominator by the conjugate of the denominator [tex]\(\sqrt{3} - 1\)[/tex]:
[tex]\[ \tan 15^\circ = \frac{(\sqrt{3} - 1)(\sqrt{3} - 1)}{(\sqrt{3} + 1)(\sqrt{3} - 1)} = \frac{(\sqrt{3} - 1)^2}{(\sqrt{3})^2 - 1^2} \][/tex]
[tex]\[ \tan 15^\circ = \frac{3 - 2\sqrt{3} + 1}{3 - 1} = \frac{4 - 2\sqrt{3}}{2} = 2 - \sqrt{3} \][/tex]
Thus, we have:
[tex]\[ \tan \left( \frac{\pi}{12} \right) = 2 - \sqrt{3} \][/tex]
We now compare this result with the given options:
1. [tex]\(\frac{1}{2 + \sqrt{3}}\)[/tex]
2. [tex]\(\frac{1}{\sqrt{3}}\)[/tex]
3. [tex]\(\frac{3}{\sqrt{3}}\)[/tex]
4. [tex]\(\frac{1}{2 - \sqrt{3}}\)[/tex]
Evaluating the first option:
[tex]\[ \frac{1}{2 + \sqrt{3}} \][/tex]
We need to rationalize the denominator by multiplying by [tex]\(2 - \sqrt{3}\)[/tex]:
[tex]\[ \frac{1}{2 + \sqrt{3}} \cdot \frac{2 - \sqrt{3}}{2 - \sqrt{3}} = \frac{2 - \sqrt{3}}{(2 + \sqrt{3})(2 - \sqrt{3})} = \frac{2 - \sqrt{3}}{4 - 3} = 2 - \sqrt{3} \][/tex]
Now, we see that:
[tex]\[ \tan \left(\frac{\pi}{12}\right) = 2 - \sqrt{3} = \frac{1}{2 + \sqrt{3}} \][/tex]
Thus, the correct answer is the first option:
[tex]\[ \boxed{\frac{1}{2 + \sqrt{3}}} \][/tex]
The angle [tex]\(\frac{\pi}{12}\)[/tex] radians can be expressed in degrees as [tex]\(15^\circ\)[/tex] since [tex]\(\frac{180^\circ}{12} = 15^\circ\)[/tex].
Using known trigonometric identities, one approach to find [tex]\(\tan 15^\circ\)[/tex] is recognizing that [tex]\(15^\circ\)[/tex] can be represented as the difference between two familiar angles: [tex]\(45^\circ\)[/tex] and [tex]\(30^\circ\)[/tex]. Therefore, we can use the tangent subtraction formula:
[tex]\[ \tan(a - b) = \frac{\tan a - \tan b}{1 + \tan a \tan b} \][/tex]
For [tex]\(a = 45^\circ\)[/tex] and [tex]\(b = 30^\circ\)[/tex]:
[tex]\[ \tan 15^\circ = \tan (45^\circ - 30^\circ) = \frac{\tan 45^\circ - \tan 30^\circ}{1 + \tan 45^\circ \tan 30^\circ} \][/tex]
We know the tangent values:
[tex]\[ \tan 45^\circ = 1 \quad \text{and} \quad \tan 30^\circ = \frac{1}{\sqrt{3}} \][/tex]
Substituting these into the formula gives us:
[tex]\[ \tan 15^\circ = \frac{1 - \frac{1}{\sqrt{3}}}{1 + 1 \cdot \frac{1}{\sqrt{3}}} = \frac{1 - \frac{1}{\sqrt{3}}}{1 + \frac{1}{\sqrt{3}}} \][/tex]
To simplify the fraction, we'll first combine the terms in the numerator and denominator to have a common denominator of [tex]\(\sqrt{3}\)[/tex]:
[tex]\[ \tan 15^\circ = \frac{\frac{\sqrt{3} - 1}{\sqrt{3}}}{\frac{\sqrt{3} + 1}{\sqrt{3}}} = \frac{\sqrt{3} - 1}{\sqrt{3} + 1} \][/tex]
Next, we rationalize the denominator by multiplying both the numerator and the denominator by the conjugate of the denominator [tex]\(\sqrt{3} - 1\)[/tex]:
[tex]\[ \tan 15^\circ = \frac{(\sqrt{3} - 1)(\sqrt{3} - 1)}{(\sqrt{3} + 1)(\sqrt{3} - 1)} = \frac{(\sqrt{3} - 1)^2}{(\sqrt{3})^2 - 1^2} \][/tex]
[tex]\[ \tan 15^\circ = \frac{3 - 2\sqrt{3} + 1}{3 - 1} = \frac{4 - 2\sqrt{3}}{2} = 2 - \sqrt{3} \][/tex]
Thus, we have:
[tex]\[ \tan \left( \frac{\pi}{12} \right) = 2 - \sqrt{3} \][/tex]
We now compare this result with the given options:
1. [tex]\(\frac{1}{2 + \sqrt{3}}\)[/tex]
2. [tex]\(\frac{1}{\sqrt{3}}\)[/tex]
3. [tex]\(\frac{3}{\sqrt{3}}\)[/tex]
4. [tex]\(\frac{1}{2 - \sqrt{3}}\)[/tex]
Evaluating the first option:
[tex]\[ \frac{1}{2 + \sqrt{3}} \][/tex]
We need to rationalize the denominator by multiplying by [tex]\(2 - \sqrt{3}\)[/tex]:
[tex]\[ \frac{1}{2 + \sqrt{3}} \cdot \frac{2 - \sqrt{3}}{2 - \sqrt{3}} = \frac{2 - \sqrt{3}}{(2 + \sqrt{3})(2 - \sqrt{3})} = \frac{2 - \sqrt{3}}{4 - 3} = 2 - \sqrt{3} \][/tex]
Now, we see that:
[tex]\[ \tan \left(\frac{\pi}{12}\right) = 2 - \sqrt{3} = \frac{1}{2 + \sqrt{3}} \][/tex]
Thus, the correct answer is the first option:
[tex]\[ \boxed{\frac{1}{2 + \sqrt{3}}} \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.